2021
DOI: 10.1101/2021.07.13.452219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dicamba drift alters plant-herbivore interactions at the agro-ecological interface

Abstract: Natural populations evolve in response to biotic and abiotic changes in their environment, which shape species interactions and ecosystem dynamics. Agricultural systems can introduce novel conditions via herbicide exposure to non-crop habitats in surrounding fields. While herbicide drift is known to produce a variety of toxic effects in plants, little is known about its impact on non-target wildlife species interactions. In a two-year study, we investigated the impact of herbicide drift on plant-herbivore inte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 71 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…Our results thus show heterogeneity in herbivory between species given dicamba exposure, and importantly, demonstrate that conclusions drawn from one weed cannot be used to generalize how dicamba drift may influence herbivory in other weeds. Further, a separate experiment using A. theophrasti found a nonsignificant increase in the proportion of chewing herbivory when plants were exposed to dicamba drift, again in a common garden field setting (Johnson and Baucom, 2022), potentially suggesting that results may be heterogeneous between experiments, whether due to changes in herbivore abundance or some other, unexamined environmental factor. While not chewing herbivory, this previous work also found that A. theophrasti exposed to dicamba drift exhibited higher abundance of whitefly larvae – a result that was replicated between two field seasons (Johnson and Baucom, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our results thus show heterogeneity in herbivory between species given dicamba exposure, and importantly, demonstrate that conclusions drawn from one weed cannot be used to generalize how dicamba drift may influence herbivory in other weeds. Further, a separate experiment using A. theophrasti found a nonsignificant increase in the proportion of chewing herbivory when plants were exposed to dicamba drift, again in a common garden field setting (Johnson and Baucom, 2022), potentially suggesting that results may be heterogeneous between experiments, whether due to changes in herbivore abundance or some other, unexamined environmental factor. While not chewing herbivory, this previous work also found that A. theophrasti exposed to dicamba drift exhibited higher abundance of whitefly larvae – a result that was replicated between two field seasons (Johnson and Baucom, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Further, a separate experiment using A. theophrasti found a nonsignificant increase in the proportion of chewing herbivory when plants were exposed to dicamba drift, again in a common garden field setting (Johnson and Baucom, 2022), potentially suggesting that results may be heterogeneous between experiments, whether due to changes in herbivore abundance or some other, unexamined environmental factor. While not chewing herbivory, this previous work also found that A. theophrasti exposed to dicamba drift exhibited higher abundance of whitefly larvae – a result that was replicated between two field seasons (Johnson and Baucom, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations